Genetic Privacy and Data Protection: A Review of Chinese Direct-to-Consumer Genetic Test Services - Du, Li; Wang, Meng (Frontiers in Genetics, 2020)
Background The existing literature has not examined how Chinese direct-to-consumer (DTC) genetic testing providers navigate the issues of informed consent, privacy, and data protection associated with testing services. This research aims to explore these questions by examining the relevant documents and messages published on websites of the Chinese DTC genetic test providers. Methods Using Baidu.com, the most popular Chinese search engine, we compiled websites of providers who offer genetic testing services and analyzed available documents related to informed consent, the terms of services, and the privacy policy. The analyses were guided by the following perspectives: the methods available for purchasing testing products; methods providers obtain informed consent; privacy issues and measures for protecting consumers’ health information; the policy for third-party data sharing; consumers right to their data; the liabilities in the event of a data breach. Results 68.7% of providers offer multiple channels for purchasing genetic testing products, and that social media has become a popular platform to promote testing services. Informed consent forms are not available on 94% of providers’ websites and a privacy policy was only offered by 45.8% of DTC genetic testing providers. 39 providers mentioned that they used measures to protect consumers’ information, of which, 29 providers had distinguished consumers’ general personal information from their genetic information. 33.7% of providers stated that with consumers’ explicit permissions, the providers could reuse and share the clients’ information for non-commercial purposes. 23 providers granted consumer rights to their health information, with the most frequently mentioned right being the consumers’ right to decide how their data can be used by providers. 21.7% of providers clearly stated their liabilities in the event of a data breach, placing more emphasis on the providers’ exemption from any liability. Conclusions Currently, the Chinese DTC genetic testing business is running in a regulatory vacuum, governed by a self-regulation mechanism. The government should develop a comprehensive legal framework to regulate DTC genetic testing offerings. Regulatory improvements should be made based on periodical reviews of the supervisory strategy to meet the rapid development of the DTC genetic testing industry.